Dioctophyma renale in a Bitch - Treatment with Unilateral Total Nephrectomy - Grendene Zanardo, Letícia Helena; Borges Szarblewski, Raquel; da Silva Ostrowski, Bruno; Ribeiro, Liana Thayse; Masiero Biassusi, Victoria; Tagliari, Nelson Junior; Giglio, Camila; Zafalon-Silva, Bruna (Acta Scientiae Veterinariae, 2024)
Background: Urinary dysfunction in domestic dogs is commonly seen in conventional pet clinics, and is often a result of inadequate food or environmental management. Parasitism by Dioctophyma renale is among the causes of urinary disorders for which surgical intervention is indicated as the therapy of choice. Dioctophymatosis is a zoonotic parasitic disease that affects domestic and wild animals, as well as humans, and is characterized by the development of D. renale in the host's body, with particular tropism for the kidney. The present study reports a case of total nephrectomy for the treatment of dioctophymatosis in a canine patient. Case: A 1-year-and-6-month-old mixed-breed bitch, weighing 6.9 kg, with a history of living indoors, presented with persistent hematuria was sent for treatment at the UniRitter Veterinary Medical Complex. During the physical examination, the patient did not present any noteworthy changes in vital parameters, such as heart rate, respiratory rate, and mucous membrane color. Abdominal ultrasonography revealed anechoic tubular structures in the right kidney surrounded by a hyperechogenic capsule, and urinalysis revealed the presence of eggs compatible with D. renale. Since no effective drug therapy currently exists for dioctophymatosis, the patient was hospitalized for surgical treatment and underwent total unilateral nephrectomy with excision of the right kidney. A pre-retroumbilical incision was made to access the cavity and expose the right kidney, which was subsequently isolated using compresses. Double ligations were performed using 3-0 mononylon for the renal artery and vein, and 3-0 polyglactin 910 for the ureter. Two nematodes were isolated from the excised kidney: 1 male measuring approximately 16 cm and 1 female measuring 36 cm. The affected kidney was consumed by the parasites, with several visible adhesions and only the capsule remaining. During the intra- and postoperative periods, no complications were observed and the patient was discharged to continue postoperative treatment at home. Fourteen days after surgery, remission of clinical signs was observed, culminating in clinical discharge. Discussion: The patient in this case had a prior history of living abroad, with wandering behavior, owing to the lifestyle of her former guardian. This aligns with the fact that dioctophymatosis mainly affects animals that live outside their homes, particularly in rural areas. Aquatic annelids, fish, and amphibians are considered vectors of the worm, as they can carry the larval stage, and thus, ingestion of these vectors, owing to poor eating habits, can lead to host contamination. Dioctophymatosis is most frequently reported to affect the kidney of its host because of the proximity of this organ to the stomach and duodenal wall, the points from which the larva can migrate. The disease is, for the most part, asymptomatic, making its diagnosis difficult. However, in the present study, the patient presented with persistent hematuria, necessitating rapid veterinary care. In this case, early diagnosis of the disease, together with carrying out complementary examinations, enabled adequate treatment through unilateral total nephrectomy. This procedure was considered to be the best option and resulted in the resolution of the disease, with the patient being clinically discharged 14 days after the procedure. Keywords: dioctophymatosis, kidney, parasitism, renal surgery, urinary. Título: Dioctophyma renale em uma cadela - tratamento com nefrectomia total unilateral Descritores: dioctofimatose, rim, parasitismo, cirurgia renal, urinário.